MENJADIKAN SANTUN BERBAHASA MELALUI PENGETAHUAN PEMEROLEHAN BAHASA ANAK - Arisul Ulumuddin; Eva Ardiana I; Azzah Nayla (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2014)
Language acquisition is the process by which someone can speak or process in general children acquire their first language. The acquisition of language in children aged two to three years to occur naturally. The acquirer is usually the natural language meaning that language acquisition occurs naturally unwittingly that a child acquire language, but just be aware of the fact that he was using language to communicate. Communication with the language that will create decent child in the language, the language has a very important role in shaping the character of manners, politeness importance of language acquisition in the family or in the community so that the child will become a full human decency.Keywords: polite language, child language acquisition.